Street Meditations: On Poetry, Street Photography and Everyday Life in Hong Kong - Tay, Chinese University of Hong Kong, Eddie (Asiatic: IIUM Journal of English Language and Literature, 2012)
This paper is part of an ongoing auto-ethnographic project to do with writing poetry and taking photographs in Hong Kong. As a poet who is interested in the aesthetic potential of visual images, I am intrigued by what Michel de Certeau calls the â€œabsent figure,â€ a figure often obscured by techniques and rationalities that govern the everyday life of the urban city that is Hong Kong (vi). If art is about the salvaging of meaning, then it is in league with everyday life, to the extent that artistic works become transgressive and predatory mediums. Poems and photographs are regarded here as forms that usurp the material spaces of Hong Kong. In this way, one is led to consider the possibilities of cultural production as a kind of furtive production wherein the everyday life of Hong Kong is made to speak.